Fabrication of biomimetic scaffold through hybrid forming technique - Celik, Dilek; Ustundag, Cem Bulent (WILEY, 2024)
Bone tissue engineering procedures require the use of a scaffold with a sufficiently porous structure, which serves as a three-dimensional template for cell attachment, followed by tissue regeneration and vascularization both in vitro and in vivo. This study aimed to create scaffold material with a unique hybrid forming that met these parameters. Slip casting and freeze-drying processes were used with a hybrid forming approach to create a bone scaffold based on hydroxyapatite (HA) mimicking the structure of cortical and cancellous bones, respectively. HA was synthesized by the wet chemical precipitation method. Fourier-transform infrared spectroscopy, dynamic light scattering, X-ray diffraction, thermogravimetric analysis-differential thermal analysis, Brunauer-Emmett-Teller, He Pycnometer, and scanning electron microscope analyses were performed to characterize the scaffold. According to analysis results, HA particle size was found at 137.8 nm. The optimum sintering temperature was determined to be 1300 degrees C. The specific surface area of the HA powder was measured as 55.11 m2/g. The total open porosity of the hybrid scaffold was calculated as 70%. Scaffold successfully substituted both cancellous and cortical layers of bone regarding structural characteristics, porosity, and mechanical strength. Considering morphological characteristics, a hybrid scaffold might facilitate vascularization, osteoinduction, and osteoconduction. Research findings suggest that the hybrid design strongly resembled natural bone and is suitable for both load-bearing and non-bearing bones.
Keywords: bone tissue engineering; freeze-drying; hybrid forming; slip-casting; OF-THE-ART; HYDROXYAPATITE NANOPARTICLES; BONE; DESIGN; Materials Science